ANALISIS RASIO KEUANGAN UNTUK MEMPREDIKSI KONDISI FINANCIAL DISTRESS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Sulistyani Sulistyani; Deny Ismanto (Universitas Ahmad Dahlan, 2017)
Financial distress precedes bankruptcy. Most financial distress models actually rely on bankruptcy data, which is easier to obtain. The purpose of this research to examine financial ratios that predict financial distress condition of a firm. The sample of this research consist of 14 distress firm and 79 non-distress firms, chosen by purposive sampling. The statistic method which is used to test on the research hypothesis is logistic regresion. The results show that the liquidity ratio (current assets/current liabilities) and a leverage ratio (current leabilities/total asset) is a significant variable to determine of financial distress firms. When profitability ratio (net income/net sales) and price earning ratio (market price per share/earnings per share) are not significant variables to determine of financial distress.